1999
DOI: 10.1002/(sici)1521-2254(199901/02)1:1<56::aid-jgm5>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct Immunologic activities of CpG DNA and implications for gene therapy

Abstract: Vertebrate immune systems have evolved the ability to detect and be activated by most microbial and viral DNAs by virtue of their content of unmethylated ‘CpG motifs’, which are selectively suppressed in vertebrate DNA. Because their CpGs are also unmethylated, the DNA in gene therapy vectors routinely induces direct immune stimulation through activating this host defense mechanism. Administration of such ‘CpG DNA’ by injection or inhalation triggers rapid activation of B cells, monocytes, macrophages, dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(35 citation statements)
references
References 70 publications
(65 reference statements)
1
34
0
Order By: Relevance
“…30,32 The presence of DNA endonucleases in muscle degraded 99% of unformulated plasmid within 90 min of delivery. 25 During plasmid delivery via EP, poly-L-glutamate may enhance plasmid uptake by neutralizing processes that normally deactivates exogenous DNA, such as degradation by nucleases or the binding to cationic entities in interstitial fluid. It is interesting to note that plasmid formulated with poly-L-glutamate showed similar levels of transgene expression as plasmid in saline when EP was omitted after i.m.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…30,32 The presence of DNA endonucleases in muscle degraded 99% of unformulated plasmid within 90 min of delivery. 25 During plasmid delivery via EP, poly-L-glutamate may enhance plasmid uptake by neutralizing processes that normally deactivates exogenous DNA, such as degradation by nucleases or the binding to cationic entities in interstitial fluid. It is interesting to note that plasmid formulated with poly-L-glutamate showed similar levels of transgene expression as plasmid in saline when EP was omitted after i.m.…”
Section: Discussionmentioning
confidence: 90%
“…25,26 Therefore, the optimal delivery system to introduce plasmid into skeletal muscle would ideally allow substantial levels of transgene expression with a minimal amount of DNA administered. In our search for such systems, the effect of excess plasmid mass 27 was assessed to determine if the presence of a 'silent' DNA could increase transgene expression.…”
Section: Addition Of Empty Plasmid Increased Reporter Gene Expressionmentioning
confidence: 99%
“…On the other hand, several studies have revealed that lipoplexes (Dow et al, 1999;Yew et al, 1999;Kako et al, 2008) encapsulating bacterially derived plasmid DNA can induce strong activation of macrophages and subsequent production of high levels of proinflammatory cytokines after intravenous administration. The activation of macrophages is mediated by the strong immunostimulatory effect of unmethylated CpG sequences present at high frequency in bacterially derived plasmid DNA (Krieg, 1999(Krieg, , 2000. To reduce the inflammation response induced by plasmid DNA, depletion of macrophages before systematic administration has been proven to be an effective approach to enhance gene transfection efficiency of lipoplexes (Sakurai et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This would, of course, reduce the risk of adverse immunologic reactions from both the carrier system, as well as the plasmid itself, especially by immunostimulatory CpG motifs. 45 As with all gene therapy strategies, the SB system is associated with some potential problems. In particular, the observed random genomic integration could result in insertional mutagenesis as well as inactivation of an essential gene(s).…”
Section: Nonviral Methods Of Liver-directed Gene Therapy Sleeping Beamentioning
confidence: 99%
“…73,74 Moreover, methylated CpG motifs within the DNA molecules also may increase the likelihood of immune response and subsequent removal of complexes. 45 Interestingly, it has been proposed recently that the liver parenchymal cells internalize naked DNA by receptor-mediated endocytosis, 75 although specific receptor(s) have not been identified. Direct injection of naked plasmid DNA into the liver of cats and rats produced expression of different reporter genes, as well as human ␣1-antitrypsin.…”
Section: Antisensementioning
confidence: 99%